2008
DOI: 10.1002/edn.122
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of blood glucose: psychological barriers and benefits

Abstract: Diabetes is to a large extent a self‐managed disease and, in this context, self‐monitoring of blood glucose (SMBG) is essential, at least for insulin‐treated patients. In practice, the uptake of SMBG is generally low: many patients fail to self‐regulate their treatment appropriately. By contrast, a minority of diabetes patients very frequently self‐test their blood glucose levels each day to achieve strict glycaemic control. These differences in usage of self‐monitoring are largely explained by psychological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
2
19
0
1
Order By: Relevance
“…Of those reporting a reduced frequency of testing, a considerable proportion reported pain as the reason and this is consistent with previous research with avoidance of insulin injections. 11 A USA based study found that 6% (of 1895 participants), reported fear of needles as a reason for reduced testing, and of the participants not monitoring their blood glucose, 14% reported a fear of needles. 12 In the present study (Table 3), 32% of the total group avoided glucose testing due to either dislike (with no reason stated) or injection pain, while 26% forgot or cited 'laziness'.…”
Section: Discussionmentioning
confidence: 99%
“…Of those reporting a reduced frequency of testing, a considerable proportion reported pain as the reason and this is consistent with previous research with avoidance of insulin injections. 11 A USA based study found that 6% (of 1895 participants), reported fear of needles as a reason for reduced testing, and of the participants not monitoring their blood glucose, 14% reported a fear of needles. 12 In the present study (Table 3), 32% of the total group avoided glucose testing due to either dislike (with no reason stated) or injection pain, while 26% forgot or cited 'laziness'.…”
Section: Discussionmentioning
confidence: 99%
“…These insights can help professionals support the patients in their self-management regarding SMBG [16,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…8,15 Questionnaires that assess fear of testing can be used to identify patients who may benefit from psychological therapy. 88 Problem solving techniques 15 and motivational interviewing are useful strategies to increase adherence with SMBG. 89 Minimizing pain with alternative lancing devices, 90 alternative site testing, 91,92 or flash glucose monitoring systems, 93 may encourage testing.…”
Section: Addressing Barriers To Technology Use and Strategies To Optimentioning
confidence: 99%
“…14 A 5-step bio-psychosocial model of SMBG facilitates understanding of testing barriers: 15 Step 1 is the decision to test: Some patients having extreme coping styles, with "blunters" who skip testing to avoid getting poor results and "monitors," who test excessively, driven by fear and anxiety.…”
mentioning
confidence: 99%